2012
DOI: 10.1007/s12194-012-0157-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of GATE Monte Carlo simulation for a dual-head gamma camera

Abstract: GATE is a simulation code which is based on the Geant4 Monte Carlo code. This code was developed for simulation of nuclear medicine imaging systems. Our aim in this study was to use and validate GATE for simulating a Siemens E.Cam gamma camera. A dual-head gamma camera was used for modeling with GATE. Each head consisted of a collimator, aluminum layer, crystal, and head shielding. The back compartment consisted of photomultiplier tubes and electronic circuits behind the crystal. The photoelectric effect and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…There are also always some minor differences in the composition, thickness, and dimensions of the actual components of the systems to be simulated with parameters provided by the manufacturers. Also, digitizer and readout parameters can affect the simulated results [19]. However, the electromagnetic physical processes are correctly modeled within GEANT4, hence that GATE is reliable from this point of view.…”
Section: Discussionmentioning
confidence: 99%
“…There are also always some minor differences in the composition, thickness, and dimensions of the actual components of the systems to be simulated with parameters provided by the manufacturers. Also, digitizer and readout parameters can affect the simulated results [19]. However, the electromagnetic physical processes are correctly modeled within GEANT4, hence that GATE is reliable from this point of view.…”
Section: Discussionmentioning
confidence: 99%
“…This simulation toolkit provides flexibility and simplicity in defining an input for simulating a complex geometry of both SPECT and PET cameras. The most important property of GATE is the ability to simulate time-dependent phenomena such as source decay, dynamic acquisitions, and movement components of the gamma [16][17][18]. Figure 5 illustrates a 3D model of the HiReSPECT system simulated in the GATE environment.…”
Section: Gatementioning
confidence: 99%
“…The GE DST-Xli was also investigated in high energy radioisotope simulations, alongside the GE Millennium VG scanner (GE) 10. A more recent study by Momennezhad et al 11 reported the development of a dual-headed Siemens E.Cam gamma camera system using GATE.…”
Section: Introductionmentioning
confidence: 99%